Organizational transparency and employees’ organizational perceptions - Stuckey, Leah Shely Klos (Kansas State University, 2024)
The current study investigated the impact organizational transparency, mediated through authentic leadership, has on employee’s perceived organizational support, trust, and cynicism through the lens of sensemaking and identification theory. Path analysis was used to test these key hypotheses. Results indicated transparency was positively related to support and trust, but was negatively related to cynicism with authentic leadership only mediating the latter. The present study also examined how differences in the organizational communications during a crisis (i.e., COVID) are perceived in terms of level of transparency, with the goal of identifying potential efforts organizations can adopt to improve their employee’s perceptions of organizational transparency. An ANCOVA was utilized to examine how the differences in a fictitious companies’ level of transparency when communicating COVID rates were perceived while controlling for fear of COVID. The results revealed that, in general, ratings of perceived transparency were higher for organizational communication conditions with more elements of transparency present. Overall, the present study provides evidence that organizational transparency does influence employees’ perceptions of their organization and sheds light on a potential viable organizational strategy to deal and communicate with their employees about COVID. Future research should explore if these findings translate to communications about other crises such as future pandemics, recessions, company layoffs, and leadership changes.
Keywords: Organizational transparency; Authentic leadership; Perceived organizational support; Perceived organizational trust; Organizational cynicism